Influence of commonly used pharmaceutical agents on equine bone marrow‐derived mesenchymal stem cell viability. (24th June 2016) - Edmonds, R. E.; Garvican, E. R.; Smith, R. K. W.; Dudhia, J.
Summary: Reason for performing study: To provide evidence to support recommendations regarding the co‐administration of drugs with mesenchymal stem cell (MSC) therapy. Objectives: To determine the influence of sedatives, local anaesthetic and corticosteroids on MSC viability and proliferation, in comparison to somatic cells derived from tendon (TDCs). Study design: In vitro cell culture. Materials and methods: MSCs (n = 3) and TDCs (n = 2) were cultured in media containing a clinically relevant dose range of xylazine, romifidine, detomidine and butorphanol, mepivacaine, methylprednisolone, or triamcinolone acetonide. Cell viability in suspension culture was assessed at intervals up to 4 h using the trypan blue dye assay. MSCs in monolayer culture were exposed to the highest concentrations of drug and proliferation was measured using the alamarBlue fluorescence assay. Results: Exposure to romifidine or mepivacaine did not significantly affect viability or proliferation rate of MSCs or TDCs at any of the dosages tested. At the highest concentration of detomidine and butorphanol, MSC viability was significantly reduced compared to controls. Although xylazine exposure caused a significant (P < 0.001), dose‐dependent reduction in MSC viability compared to controls, overall population viability remained good. Conversely, both methylprednisolone and triamcinolone resulted in the rapid death of significant numbers of MSCs (P < 0.001). Conclusions: Clinicians can sedate horses and administer nerve blocks to assist in intratendinous or intrathecal injection of MSCs with confidence that these drugs will not impact the viability of implanted cells. However, the concomitant use of corticosteroids is likely to have a severely detrimental effect on cell viability and should not be performed. Similarly, steroid administration into the sheath of a damaged tendon is not recommended.